THE IMPACT OF BOYCOTT ON FINANCIAL PERFORMANCE AND MARKET REACTION AT PT UNILEVER INDONESIA - Hotmauli Rajagukguk (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study aims to analyze the impact of the boycott of PT Uniliver Indonesia affiliated with pro-israel on financial performance and market reaction. Data was collected through analysis techniques using financial ratios such as Return on Asset (ROA), Return on Equity (ROE), Current Ratio and Debt to Equity ratio (DER) and analysis of stock price movements. The results showed that ROA decreased after the boycott due to decreased net income compared to total assets. The company's Current Ratio decreased after the boycott, due to current debt greater than the current assets owned by the company. However, ROE has increased after the boycott due to the expenses earned by the company not considering the capital working in the company. DER has increased due to the company's inaccuracy in taking production capital and marketing processes. And the results of the stock price movement are in a condition that tends to decline. This study provides results that the boycott of pro-Israel affiliated products has a significant impact on several aspects of the company's financial performance and Market Reaction.